2020
DOI: 10.7759/cureus.10438
|View full text |Cite
|
Sign up to set email alerts
|

Whole Breast Invasive Lobular Carcinoma Not Detected Radiographically

Abstract: Breast cancer is the most commonly occurring cancer in women, with invasive lobular carcinoma being the second most common histologic form. A 78-year-old female patient presented complaining of an enlarged palpable lymph node in the left axilla. Breast ultrasound, digital mammography, and contrast-enhanced spectral mammography (CESM) revealed no abnormal findings. Core needle biopsy of the lymph node revealed infiltrative, diffuse neoplastic growth suggestive of adenocarcinoma, indicating that the primary site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…While Selinko et al reported higher US sensitivity in detecting ILC, they also reported a 28% increase in detecting smaller lesions on mammography (1 cm), especially when they appeared as spiculated masses [ 6 ]. In the case report by Vlastarakos, the tumor measured 23 mm on breast MRI but was not detected on mammography [ 19 ]. There are few studies addressing non-enhancing ILC on MRI, which are summarized in Table 1 [ 8 , 9 , [20] , [21] , [22] ].…”
Section: Discussionmentioning
confidence: 99%
“…While Selinko et al reported higher US sensitivity in detecting ILC, they also reported a 28% increase in detecting smaller lesions on mammography (1 cm), especially when they appeared as spiculated masses [ 6 ]. In the case report by Vlastarakos, the tumor measured 23 mm on breast MRI but was not detected on mammography [ 19 ]. There are few studies addressing non-enhancing ILC on MRI, which are summarized in Table 1 [ 8 , 9 , [20] , [21] , [22] ].…”
Section: Discussionmentioning
confidence: 99%